Trends of Transformational Leadership Dimensions in Indonesia Islamic Educational Institutions (2019-2024) - Ratri Harida; Binti Maumah; Acmad Patoni (Institut Agama Islam Negeri Imam Bonjol Padang, 2024)
According to Bass and Avolio, there are four dimensions of transformational leadership. These dimensions include idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The application of the transformational leadership dimension in the setting of Islamic educational institutions in Indonesia can help improve the quality of education and student character building in a holistic way. This systematic library review research focuses on trends in topics, research objects, and types of transformational leadership dimensions reviewed in scientific papers published in 2019–2024. The study aims to provide a comprehensive overview of the application of the transformational leadership dimension to Islamic education in Indonesia over the past five years. Topics that associate quality education with the application of transformational leadership dimensions are most widely reviewed in scientific papers published in 2019–2024. The next finding is research related to the application of transformational leadership dimensions more effectively in the setting of MTs (junior high school). Idealized influence is the type of transformational leadership dimension most mentioned in the article on the implementation of the transformational leadership dimension in 2019–2024. Further researchers can undertake further studies on the implementation of the transformational leadership dimension on other related topics, setting up different institutions, and deeper exploration of the types of transformative leadership dimensions that can affect the performance of Islamic educational institutions as a whole.